Defining an Intraoperative Hypotension Threshold in Association with Stroke in Cardiac Surgery. (September 2018) - Sun, Louise Y.; Chung, Amy M.; Farkouh, Michael E.; van Diepen, Sean; Weinberger, Jesse; Bourke, Michael; Ruel, Marc
Abstract : What We Already Know about This Topic: Ischemic stroke after cardiac surgery is a devastating complication affecting approximately 2% of patients The relationship between hypotension occurring before, during, and after cardiopulmonary bypass and stroke remains unclear What This Article Tells Us That Is New: Mean arterial pressure less than 65 mmHg for 10 or more min during cardiopulmonary bypass is associated with an increased risk of stroke Even mild relative hypotension, defined as a less than 10% decrease from preinduction baseline during bypass, was also associated with an increased risk of stroke Background: Stroke is a leading cause of morbidity, mortality, and disability in patients undergoing cardiac surgery. Identifying modifiable perioperative stroke risk factors may lead to improved patient outcomes. The association between the severity and duration of intraoperative hypotension and postoperative stroke in patients undergoing cardiac surgery was evaluated. Methods: A retrospective cohort study was conducted of adult patients who underwent cardiac surgery requiring cardiopulmonary bypass at a tertiary center between November 1, 2009, and March 31, 2015. The primary outcome was postoperative ischemic stroke. Intraoperative hypotension was defined as the number of minutes spent within mean arterial pressure bands of less than 55, 55 to 64, and 65 to 74 mmHg before, during, and after cardiopulmonary bypass. The association between stroke and hypotension was examined by using logistic regression with propensity score adjustment. Results: Among the 7, 457 patients included in this analysis, 111 (1.5%) had a confirmed postoperative diagnosis of stroke. Stroke was strongly associated with sustained mean arterial pressure of less than 64 mmHg during cardiopulmonary bypass (adjusted odds ratio 1.13; 95% CI, 1.05 to 1.21 for every 10 min of mean arterial pressure between 55 and 64 mmHg; adjusted odds ratio 1.16; 95% CI, 1.08 to 1.23 for every 10 min of mean arterial pressure less than 55 mmHg). Other factors that were independently associated with stroke were older age, hypertension, combined coronary artery bypass graft/valve surgery, emergent operative status, prolonged cardiopulmonary bypass duration, and postoperative new-onset atrial fibrillation. Conclusions: Hypotension is a potentially modifiable risk factor for perioperative stroke. The study's findings suggest that mean arterial pressure may be an important intraoperative therapeutic hemodynamic target to reduce the incidence of stroke in patients undergoing cardiopulmonary bypass. Abstract : Mean arterial pressure less than 65 mmHg for 10 or more min during cardiopulmonary bypass is associated with an increased risk of stroke. Even mild relative hypotension, defined as a less than 10% decrease from preinduction baseline during bypass, was also associated with an increased risk of stroke.